(untitled) (I-Finance: a Research Journal on Islamic Finance, 2025)
The purpose of this study was to determine and analyze the effect of profitability, company size and dividend policy on firm value. The population and sample are all companies that have sharia shares listed on the Indonesia Stock Exchange as many as 20 companies. Based on this, the sample used is based on the criteria so that a sample of 17 companies is obtained. The analysis technique uses panel data regression with the help of the STATA 17 application with hypothesis testing using the t test and F test. The test results show that profitability affects firm value, firm size variables affect firm value, dividend policy variables affect firm value and simultaneously profitability variables, firm size and dividend policy affect stock prices. The conclusion that can be drawn is that both partially and simultaneously the variables of profitability, company size and stock price affect the stock price.